Successful response in a case of severe pustular psoriasis after interleukin‐1β inhibition. (1st January 2017) - Skendros, P.; Papagoras, C.; Lefaki, I.; Giatromanolaki, A.; Kotsianidis, I.; Speletas, M.; Bocly, V.; Theodorou, I.; Dalla, V.; Ritis, K.
Summary: Generalized pustular psoriasis (GPP) is a severe type of psoriasis accompanied by systemic and often life‐threatening manifestations. The efficacy of the interleukin (IL)‐1 antagonist anakinra in cases of GPP underscores the role of IL‐1 in disease pathogenesis. We present a case of a middle‐aged man who developed an abrupt and severe form of GPP with severe eosinophilia and cholestatic hepatitis. The patient received salvage treatment with a combination of glucocorticoids, hydroxyurea and imatinib, while administration of the IL‐1 inhibitor anakinra resulted in remission of hepatitis and a significant skin improvement. However, due to persistent hypersensitivity skin reactions, anakinra was withdrawn and replaced with the anti‐IL‐1β antagonist canakinumab. As a result of canakinumab, the patient's skin completely cleared, while no systemic manifestations recurred. After 1 year of continuous canakinumab therapy, the patient remained virtually free of symptoms, while the drug was well tolerated.